Promoting mental health among at-risk adolescents in Malaysia (MyHeRo): study protocol for a cluster randomised controlled trial to evaluate the effectiveness and cost-effectiveness of a school-based intervention compared with study skills condition for adolescents identified as at risk for anxiety and depression - Cecilia A., Essau; Suwaibah, Zakaria; Ting, Chuong Hock; Julia Ai Cheng, Lee; Alejandro de la, Torre-Luque; Alvin Lai Oon, Ng; Hazreen, Abdul Majid; Helen, Dodd; Nik Daliana, Nik Farid; Noor Azimah, Muhammad; Suzaily, Wahab (Springer Nature, 2026)
Abstract Background In Malaysia, adolescent anxiety and depression are increasing faster than ever, and rates of suicidal behaviour are rising especially among those living in deprived communities. However, Malaysia’s mental health system is currently constrained by limited workforce capacity, affecting the delivery of effective interventions. The overall aim of this trial is to use a school-based intervention to promote mental health among at-risk adolescents from low-income communities in Malaysia. Our primary aim is to evaluate the effectiveness and cost-effectiveness of a school-based intervention (“Super Skills for Life”; SSL) in reducing anxiety and depression, and in improving mental wellbeing in adolescents aged 12–14 years. We also aim to determine the characteristics of adolescents who benefit from SSL, compared to those who do not, as well as to identify contextual factors related to the successful implementation of SSL in Malaysian schools.